Exploration of children’s value patterns in relation to environmental education programmes - Kelly, Tim; Bouman, Thijs; Kemp, Simon; Wijngaarden, Franka; Grace, Randolph C. (Frontiers in Psychology, 2023)
During childhood we begin to develop values, including valuing the natural environment (biospheric values). Although biospheric values are believed to provide the foundation for pro-environmental behaviour throughout the course of one's life, little research has investigated these values in children. The present study aimed to investigate the relationships between children's endorsement of biospheric values, their pro-environmental behaviours, and their perception of their friends' and peers' endorsement of biospheric values. Moreover, we investigated whether these values and behaviours, as well as the hypothesised relationships, were affected by educational programmes that were already implemented at schools. The results showed that children generally strongly endorse biospheric values, and that biospheric values were positively related to some personal and group proenvironmental behaviours. The study also found that, as in previous research with adults, the participants believed that their friends and peers endorsed biospheric values significantly less than they themselves did. Environmental educational programs were partially effective in reducing the participants' underestimation of their friends' biospheric values and increased the likelihood of some group pro-environmental behaviours. Our findings highlight the need for further research to investigate the effects of group pro-environmental behaviours and the perception of group values.As you suggested, we have changed the title, to better reflect that the methodology does not establish cause.The Introduction was completely dissected and restructured to ensure that there was no repetition. We considered highlighting the hypotheses, but it would not fit with Frontiers' preferred format.